Reduction in myofilament Ca2+ sensitivity partially ameliorates the cardiac phenotype in hypertrophic cardiomyopathy linked to a TnT-R92Q mutation - Langa, Paulina; Bacon, Angelie; Warren, Chad M.; Chowdhury, Shamim A. K.; Halas, Monika; Fernandes, Aurelia A.; McCauley, Mark D.; Goldspink, Paul H.; Solaro, R. John; Wolska, Beata M. (Frontiers in Physiology, 2025)
Hypertrophic cardiomyopathy (HCM) is a genetic disease caused by mutations in sarcomeric proteins. Mutations in sarcomeric proteins that give rise to cardiomyopathies produce abnormalities in the biophysical properties of the sarcomere that are propagated beyond the cardiac myocyte. In this study, we evaluated the hypothesis that early desensitization of myofilament Ca2+ sensitivity in the TnT-R92Q mouse model, achieved through the introduction of pseudo-phosphorylated TnI (TnI-S23,24D or TnI-DD), may delay the progression of the HCM phenotype in cardiac myocyte and endothelial cellular compartments of the heart. We studied non-transgenic mice, transgenic (TG) mice expressing TnT-R92Q (TnT-R92Q), TG mice expressing TnI-DD, and double transgenic mice expressing TnT-R92Q and TnI-DD at 28 days and 16 weeks of age. Experiments reported here demonstrate that expression of TnI-DD in the TnT-R92Q HCM mouse model results in partial normalization of myofilament Ca2+ sensitivity, improved cardiac morphology and function, reduced fibrosis, normalization of YAP signaling in endothelial cells, but a lack of normalization of coronary flow parameters. The novelty of the approach reported here highlights that although small corrections made to offset the sarcomeric defect may not fully or immediately resolve the disease’s pathophysiologic state, they can lessen the severity of HCM. Our findings further support the concept that early desensitization of myofilaments to Ca2+ in HCM, mainly when arising from mutations in thin filament proteins, represents a promising avenue for developing new therapeutic drugs.